Sandscapes
XIV, 227 p. 23 illus., 12 illus. in color.
Keywords: Sandscapes: Writing the British Seaside reflects on the unique topography of sand, sandscapes, and the seaside in British culture and beyond. This book brings together creative and critical writings that explore the ways sand speaks to us of holidays and respite, but also of time and mortality, of plenitude and eternity. Drawing together writers from a range of backgrounds, the volume explores the environmental, social, personal, cultural, and political significance of sand and the seaside towns that have built up around it. The contributions take a variety of forms including fiction and nonfiction and cover topics ranging from sand dunes to sand mining, from seaside stories to shoreline architecture, from sand grains to global sand movements, from narratives of the setting up of bed and breakfasts to stories of seaside decline. Often a symbol of aridity, sand is revealed in this book to be an astonishingly fertile site for cultural meaning.